A biomimetic cellulose‐based composite material that incorporates the antimicrobial metal‐organic framework HKUST‐1. Issue 3 (6th August 2018) - Rickhoff, T. A.; Sullivan, E.; Werth, L. K.; Kissel, D. S.; Keleher, J. J.
ABSTRACT: The synthesis and characterization of a biomimetic composite material composed of cellulose acetate embedded with a copper‐based metal‐organic framework, MOF‐199 (HKUST‐1), is reported and has been investigated for use as an adsorbent material in water remediation. Incorporation of MOF‐199 into cellulose acetate enhances the stability of the metal‐organic framework in water allowing for a flexible and tunable polymeric material. The adsorption of methylene blue to the cellulose‐MOF199 composite was tracked spectroscopically over time and is best described by a mixed Langmuir–Freundlich isotherm adsorption model. The total remediation of methylene blue to the cellulose‐MOF199 composite is comparable to that of pure cellulose, however, it is shown herein that incorporation of MOF‐199 into cellulose acetate inhibits the growth of the Gram‐negative bacterium Escherichia coli . © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 46978. Abstract :